Entrepreneurial Cognition: Three Essays on Entrepreneurial Behavior and Cognition Under Risk and Uncertainty - Giulio Zichella (Copenhagen Business School (CBS), 2017)
Research in decision making and cognition has a long tradition in economics and management and represents a substantial stream of research in entrepreneurship. Risk and uncertainty are two characteristics of the decision environment. It has long been believed that entrepreneurs who need to make business judgments in such environments are less risk- and uncertainty-averse than non-entrepreneurs. However, this theoretical prediction has not been supported by empirical evidence. Instead, entrepreneurs have been found to be more susceptible to cognitive biases and heuristics. These cognitive mechanisms, which represent deviations from rational judgment, help entrepreneurs simplify their decision-making and carry out decisions in a timely manner. As a result, a growing stream of research in entrepreneurship focuses on the cognitive differences between entrepreneurs and non-entrepreneurs when faced with risk and uncertainty. The purpose of this dissertation is to contribute to this latter stream of research by examining how individuals differ in their cognition and behaviors in situations of risk and uncertainty in a controlled environment. More specifically, the dissertation explores how entrepreneurs and nonentrepreneurs differ in their behavioral susceptibility to prior outcomes, increasing degrees of risk, risk perception, and predictive information. The empirical analyses are based on data from a laboratory experiment that I designed and conducted in October 2014. Individuals participating in the experiment were selected based on their entrepreneurial intentions, with a high degree of comparability and a limited impact of prior entrepreneurial experience. The data include measures of behavior in situations of risk and uncertainty with real monetary incentives, risk perception, and a number of individual characteristics, including personality traits, cognitive biases, and demographics. In the first essay, I explore how individuals with and without entrepreneurial intentions differ in terms of risk behavior by testing their sensitivity to prior monetary outcomes and an increasing degree of risk. In the second essay, I explore whether individuals with and without entrepreneurial intentions differ in their risk perceptions by examining how they focus their attention on different aspects of risk, specifically either possible monetary outcomes or the probabilities of obtaining these outcomes. In the third and final essay, I test individuals' sensitivity to a lack of predictive information when making choices under uncertainty. In sum, the dissertation contributes to a more nuanced understanding of entrepreneurial cognition in situations of risk and uncertainty by illustrating the direct link between cognition and behavior. Since the dissertation focuses on individuals with limited entrepreneurial experience, it makes important practical contributions with respect to novice entrepreneurs and their cognition in cases of risk and uncertainty. As a result, it provides important insights into how entrepreneurs and non-entrepreneurs differ from a cognitive perspective.
hdl:10398/9507
Keywords: 650